Advances in group processes. Vol. 31 - Thye, Shane R.; Lawler, Edward J. (Advances in group processes., 2014)
Advances in group processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of œgroup processes. This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, exchange, justice, influence, decision-making, intergroup relations and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, philosophy, computer science, mathematics and organizational behaviour. This volume contains papers presented at the 25th anniversary of the Annual Group Processes Conference.